A game-theory-based analysis of corruption and its effects in CEE countries - Havlicek, Karel; Valenčík, Radim (Konsekwencje korupcji w krajach Europy Środkowo-Wschodniej z punktu widzenia teorii gier, 2011)
The Czech Republic occupies one of the leading positions as far as the dispersion and deep roots of corruption are concerned, and even though all parties (in the political as well as non-political sense) commit to fight it, the results of this battle are more than dismal. This contribution presents an answer to the question of why this is the case. The real problem is not corruption, which can be uncovered and punished relatively easily, but rather that which we call hyper-corruption. In the first approximation, one can say that this concerns the formation of relationships based on the “corrupting of the corrupt”, respectively the forced corruption behaviour of those who have engaged in corruption or similar forms of behaviour
Ekonomia = Economics, 2011, Nr 2 (14), s. 235-243
Keywords: corruption; conflicts of interest; game theory; economic growth